"Venomous" bites from non-venomous snakes : a critical analysis of risk and management of "colubrid" snake bites - Weinstein, Scott A. (Elsevier, 2011)
This book is the first significant contribution to thoroughly examine the potential hazards associated with snakes of the former family, Colubridae. This family contained>65% of living snake species (approximately 3,000 taxa) and has recently been split into multiple families. Many of these snakes produce oral secretions that contain toxins and other biologically-active substances. A large variety of these snakes figure in the pet industry, yet little documented information or formal study of their potential medical importance has been published. Therefore, although the possible medical importance of many of these species has been subjected to speculation since the mid-nineteenth century, there is a limited amount of useful descriptive information regarding the real hazard (or lack thereof) of snakes belonging to this diverse, artificial family. There is a need for "one-stop shopping" offering information regarding their possible toxicity and clinical relevance as well as recommendations for medical management of their bites. This book is the first synthesis of this information and includes evidence-based risk assessment, hazard rankings and specific recommendations regarding important species, many common in captivity. Fills a gap in the toxinological, medical and herpetological literature by providing a comprehensive review of this entire assemblage of snakes, with particular attention given to their capacity, real or rumored, to cause harm to humans A patient-centered, evidence-based approach is applied to analyzing documented case reports of bites inflicted by approximately 100 species. Clinical management of medically significant bites from non-front-fanged colubroids is methodically reviewed, and specific recommendations are provided